TANTANGAN DAN PERAN PEMERINTAH DALAM MENINGKATKAN PELAYANAN KESEHATAN DI KABUPATEN TAKALAR - Atma Ras; Sultan; Arsyad Genda; Dimas Ario Sumilih; Hariashari Rahim; Andi Nurlela; Syahrul Ramadhan (Journal Publicuho, 2024)
This study aims to determine the role of the village government in organizing health services in Sampulungan Village. In addition, this study also aims to determine the challenges faced by the village government and the community in the service process and accessibility to health facilities. Using a qualitative research approach with a case study strategy. The results of this study indicate that the role of the village government in health services is still very minimal, as seen from the unavailability of health centres and inadequate health facilities. The village government also lacks initiative in facilitating health services because it is hampered by the lack of participation in voicing the aspirations of the community in the village. In addition, the community's view of the role of government in the field of services, especially health, is greatly influenced by the low level of community knowledge about participation at the village apparatus level. This study also found several obstacles faced by the village government, especially in Sampulungan Village, in improving the quality of services, including social construction, power dominance, and the non-involvement of village officials in decision-making at the central and district levels. Therefore, it is important to provide education about bureaucracy in order to improve the understanding of the community and the village government of Sampulungan District regarding the quality of health services.